Методологические ограничения метода дерева событий - Пампуро, В.И. (Видавничий дім "Академперіодика" НАН України, 2008)
A short analysis of the events tree method is given, and the theoretical groundlessness of the method is proved. The incorrectness to postulate a probabilistic model of accidents is shown. The error of accident risk assessments by the events tree method is determined.